Management of care to chronic conditions in the rural under the coordination of nurses - Tamires Viviane Aparecida Diehl; Felipe Rodrigues Garcia de Souza; Vilma Constancia Fioravante dos Santos; Deise Lisboa Riquinho; Adriana Roese Ramos (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To analyze the perspective of Nurses Coordinators of Family Health Teams on the management of care for people with chronic illness in rural areas. Method Qualitative approach exploratory study, carried out in a Health Region of Rio Grande do Sul, together with the Nurses in charge of the Units, between 2014 and 2015. The sample included seven participants. Data analysis was driven by thematic categorization and using NVIVO software. Results The thematic categories identified were: The administrative political organization of health care; The pluralities of rural impose specifics on care management and Strategies for management of care in the rural areas. Final considerations We pointed out elements of care management that are related not only to individual care, but also elements related to broader dimensions of health care, such as the social and political relationships that tension over the territories and that have implications to clinical practice.